2016
DOI: 10.17077/2154-4751.1329
|View full text |Cite
|
Sign up to set email alerts
|

Sexual preventative health in US sexual minority women: a review

Abstract: Free full text article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(100 reference statements)
0
5
0
2
Order By: Relevance
“…Women who have sex with women who are cisgender (i.e. whose assigned sex at birth aligns with their current gender identity) are often inaccurately perceived to be at minimal to no risk for sexually transmitted infections (STIs) and HIV (Doull et al 2018;Gorgos and Marrazzo 2011;Matebeni 2009;Muzny et al 2013), despite research documenting equal or higher risk compared to women with exclusively male partners (Gorgos and Marrazzo 2011;McCune, Imborek and Stockdale 2017;Kerr, Ding and Thompson 2013). Studies have documented risk factors for and transmission of trichomoniasis, syphilis, hepatitis A and human papillomavirus between female sexual partners (Gorgos and Marrazzo 2011;Kerr, Ding and Thompson 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Women who have sex with women who are cisgender (i.e. whose assigned sex at birth aligns with their current gender identity) are often inaccurately perceived to be at minimal to no risk for sexually transmitted infections (STIs) and HIV (Doull et al 2018;Gorgos and Marrazzo 2011;Matebeni 2009;Muzny et al 2013), despite research documenting equal or higher risk compared to women with exclusively male partners (Gorgos and Marrazzo 2011;McCune, Imborek and Stockdale 2017;Kerr, Ding and Thompson 2013). Studies have documented risk factors for and transmission of trichomoniasis, syphilis, hepatitis A and human papillomavirus between female sexual partners (Gorgos and Marrazzo 2011;Kerr, Ding and Thompson 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, 12% (n = 54) of present study participants identified as bisexual, and 7% (n = 31) of participants identified as either somewhat, mostly, or exclusively gay. In past research, lesbian and bisexual women reported less condom use than heterosexual women (e.g., McCune et al, 2017). Little is known about bisexual and lesbian/gay Latina college students' condom use; future research should explore such partner-and relationship-specific characteristics linked with condom use (Katz et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…O dispositivo vai depender do tipo de prática sexual a ser realizada. Na penetração de dildos/vibradores, é possível utilizar o preservativo peniano quando há o compartilhamento do fômite em ambas as parceiras, diminuindo assim o contato de secreções entre elas (3) . Quando as práticas são manuais, é possível utilizar dedeiras (dispositivo de látex muitas vezes usado em fonoaudiologia), luvas ou somente os dedos da luva cortados, como preservativo de dedo.…”
Section: Introductionunclassified
“…Na prática de sexo oral ou no contato entre vaginas, existe a possibilidade do uso de plástico filme, ou preservativos peniano e vaginal/anal cortados para formação de uma barreira. Nessa prática, usa-se também dental dam que é uma folha de látex usada como barreira dental em tratamentos odontológicos (3) . Apesar de haver métodos que diminuem a exposição dessas infecções entre mulheres, a realização deles tem se confrontado, na prática, com algumas barreiras presentes tanto em âmbito pessoal (no desconhecimento das ISTs e como preveni-las) como social (na divulgação dessas práticas) na vida das mulheres que se relacionam com mulheres (3) .…”
Section: Introductionunclassified